Cardiovascular Risk Assessment and Treatment Modality in Erectile Dysfunction - Ozel, Faik (Jour Med Resh and Health Sci, 2021)
Erectile dysfunction (ED) is an important public health problem due to cardiovascular diseases (CVD), which is very common and associated with aging in men. The fact that the risk factors of CVD and ED are similar and the mechanisms in their pathophysiology are similar explains the coexistence of these two diseases. In this review, we aimed to evaluate cardiovascular risk assessment for ED patients to have a healthy sexual intercourse.